SAT0398 EVALUATION OF THE PREDICTIVITY OF THE THERAPEUTIC RESPONSE ACCORDING TO THE PRESENCE OF METABOLIC COMORBILITIES IN PATIENTS WITH PSORIASIC ARTHRITIS ON BIOTECHNOLOGY THERAPY: OBSERVATIONAL RETROSPECTIVE STUDY. (June 2019) - Parisi, Simone; Beigi, Davide Mohammad Reza; Priora, Marta; Ditto, Maria Chiara; Peroni, Clara Lisa; Laganà, Angela; Fusaro, Enrico
Abstract : Background: Psoriatic Arthritis (PsA) is a systemic chronic inflammatory disease, which leads to an increased oxidative stress and to endothelial alterations, with increased cardiovascular and metabolic risks. These conditions explain the high prevalence of myocardial infarction, cerebrovascular accidents, diabetes mellitus, obesity, steatohepatitis, alterations of lipid set and an increased prevalence of metabolic syndrome in patients with PsA. The results of other studies suggest that these comorbidities could negatively influence the disease activity and the therapy response in patients with PsA. Objectives: The aim of the study is to evaluate a population of patients with PsA treated with biological drugs (bDMARDs) and the achievement of MDA during the observation. Methods: Ninety-eight patients with PsA treatd by DMARDs from January 2016 to January 2018 were enrolled. Data were collected for 24 months of treatment, related to the check-ups performed every three months. Demographic characteristics, cardiovascular risk factors and cardio-metabolic comorbidities, disease joint involvement at baseline and the assumed therapy were analyzed. The association with the presence of MDA at 0 months and 24 months was evaluated for each of these parameters. Age and gender of patients, duration of illness and smoking habits were taken into consideration. Cardio-vascular risk factors and cardio-metabolic comorbidities selected at baseline were arterial hypertension, diabetes, obesity, hepatic steatosis, hypercholesterolemia, hypertriglyceridaemia, hyperuricaemia, cardiac disorders (myocardial infarction and atrial fibrillation) and cerebro-vascular accidents (stroke and TIA). The population was subdivided according to oligoarticular or polyarticular involvement of the disease present at baseline. As far as the therapy carried out is concerned, the patients were classified according to the class of bDMARDs (anti-TNF-α and not anti-TNF-α), the treatment line at the beginning of the observation (first line or second line and subsequent), the number of switches at 12 and 24 months and simultaneous therapy with relative average dose of drugs (methotrexate and glucocorticoids). Results: Male sex was more associated with the condition of MDA, both at baseline (p = 0.01) and at 24 months (p = 0.04). A statistically significant association between the presence of cerebro-vascular accidents (stroke and TIA) and the disease status was found at baseline: amongst patients with such comorbidity, 75% were not found in MDA at time 0 (p = 0.03). The same result was not found in relation to MDA after 24 months. No other cardio-metabolic comorbidity was associated with a worse outcome. There was no association with a better outcome for any of the two classes of biological drugs considered (anti-TNF-α and not anti-TNF-α). Polyarticular involvement was associated with a worse disease status, both at baseline (p = 0.01) and after 24 months of therapy (p = 0.04). Conclusion: In the current study, the polyarticular form of PsA present at baseline was the most associated feature (OR 0.44) with a worse outcome in a population of patients with cardio-metabolic comorbidities on bDMARDs. Cerebro-vascular accidents appeared as the only morbid condition associated with a worse state of disease at the beginning of the observation, but this correlation disappears after 24 months. This result can be justified by the immunosuppressive treatment, which decreases the risks related to the inflammatory condition characteristic of PsA. Disclosure of Interests: Simone Parisi Speakers bureau: Chiesi, Jansenn, Pfizer, Celgene, Abbvie, Lilly., Davide Mohammad Reza Beigi: None declared, Marta Priora Grant/research support from: Sanofi SpA, Maria Chiara Ditto: None declared, Clara Lisa Peroni: None declared, Angela Laganà: None declared, Enrico Fusaro Grant/research support from: Abbvie, Abiogen, Actelion, Amgen, Biogen, BMS, Celgene, Grunenthal, GSK, Janssen, Lilly, MSD, Mundipharma, Novartis, Pfizer, Roche, SANOFI, SOBI, UCB